Novel aspects of hypothalamic-pituitary-adrenal axis regulation and glucocorticoid actions - Uchoa, Ernane Torres (2014)
Normal hypothalamic-pituitary-adrenal (HPA) axis activity leading to rhythmic and episodic release of adrenal glucocorticoids is essential for body homeostasis and survival during stress. Acting through specific intracellular receptors in the brain and periphery, glucocorticoids regulate behavior, metabolic, cardiovascular, immune, and neuroendocrine activities. In contrast to chronic elevated levels, circadian and acute stress-induced increases in glucocorticoids are necessary for hippocampal neuronal survival and memory acquisition and consolidation, through inhibiting apoptosis, facilitating glutamate transmission and inducing immediate early genes and spine formation. In addition to its metabolic actions leading to increasing energy availability, glucocorticoids have profound effects on feeding behavior, mainly through modulation of orexigenic and anorixegenic neuropeptides. Evidence is also emerging that in addition to the recognized immune suppressive actions of glucocorticoids by counteracting adrenergic proinflammatory actions, circadian elevations have priming effects in the immune system, potentiating acute defensive responses. In addition, negative feedback by glucocorticoids involves multiple mechanisms leading to limiting HPA axis activation and preventing deleterious effects of excessive glucocorticoid production. Adequate glucocorticoid secretion to meet body demands is tightly regulated by a complex neural circuitry controlling hypothalamic corticotrophin releasing hormone (CRH) and vasopressin secretion, the main regulators of pituitary adrenocorticotrophic hormone (ACTH). Rapid feedback mechanisms, likely involving non-genomic actions of glucocorticoids, mediate immediate inhibition of hypothalamic CRH and ACTH secretion, while intermediate and delayed mechanisms mediated by genomic actions involve modulation of limbic circuitry and peripheral metabolic messengers. Consistent with their key adaptive roles, HPA axis components are evolutionarily conserved, being present in the earliest vertebrates. Understanding these basic mechanisms may lead to novel approaches for the development of diagnostic and therapeutic tools for disorders related to stress and alterations of glucocorticoid secretion.